2021
DOI: 10.1186/s12882-021-02522-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes after simultaneous pancreas kidney transplantation compared to kidney transplantation alone: a propensity score matching analysis

Abstract: Background Coronary heart disease due to arteriosclerosis is the leading cause of death in type 1 diabetic patients with end-stage renal disease (ESRD). The aim of this study was to evaluate the effect of simultaneous pancreas kidney transplantation (SPKT) compared to kidney transplantation alone (KTA) on survival, cardiovascular function and metabolic outcomes. Methods A cohort of 127 insulin-dependent diabetes mellitus (IDDM) patients with ESRD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Studies consistently demonstrate its superiority in prolonging patient survival, reducing the development and progression of peripheric vascular disease, and reducing mortality rates compared to alternative treatments for end-stage renal disease and insulin-dependent diabetes mellitus. [4][5][6][7] Over the last decades, SPKT outcomes have improved, thanks to technical advances, better donor and recipient selection, new immunosuppressive agents, and increased knowledge regarding the management of complications. [8][9][10][11] Despite the promising results, it should be noted that SPKT is a complex procedure that can lead to surgical complications resulting in graft loss, impaired kidney function, increased recipient mortality, and an extended hospital length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%
“…Studies consistently demonstrate its superiority in prolonging patient survival, reducing the development and progression of peripheric vascular disease, and reducing mortality rates compared to alternative treatments for end-stage renal disease and insulin-dependent diabetes mellitus. [4][5][6][7] Over the last decades, SPKT outcomes have improved, thanks to technical advances, better donor and recipient selection, new immunosuppressive agents, and increased knowledge regarding the management of complications. [8][9][10][11] Despite the promising results, it should be noted that SPKT is a complex procedure that can lead to surgical complications resulting in graft loss, impaired kidney function, increased recipient mortality, and an extended hospital length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes and diabetic ESRD continues to increase significantly in ethnic groups, including Hispanics 1,2 . A simultaneous pancreas and kidney transplant (SPKT) restores euglycemia without insulin and improves the quality of life, metabolic profiles, and cardiovascular health 3–8 . Recent studies have reported advancements in surgical techniques for pancreas transplants, resulting in fewer complications 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 A simultaneous pancreas and kidney transplant (SPKT) restores euglycemia without insulin and improves the quality of life, metabolic profiles, and cardiovascular health. [3][4][5][6][7][8] Recent studies have reported advancements in surgical techniques for pancreas transplants, resulting in fewer complications. [9][10][11] Hispanics are the largest minority in the United States (18%) and are predicted to comprise 30% of the US population by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous kidney and pancreas transplant further improves the quality of life, with a better metabolic and cardiovascular profile. 2-6…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous kidney and pancreas transplant further improves the quality of life, with a better metabolic and cardiovascular profile. [2][3][4][5][6] Although a successful pancreas transplant is associated with better glucose homeostasis and its advantages, it has a potentially increased risk of surgical complications. Most centers use a cutoff of 50 y of age as a criterion for simultaneous pancreas kidney transplantation (SPKT).…”
Section: Introductionmentioning
confidence: 99%